'Incomers' leading 'community-led' sustainability initiatives: A contradiction in terms?. (August 2019) - Creamer, Emily; Allen, Simon; Haggett, Claire
'Community' is frequently identified as an important element of sustainable development policy, with communities thought to be particularly effective spaces in which to encourage individuals to adopt sustainable lifestyles. The potential power of a community-based approach derives from the ability of community groups to tap into existing social networks and local bonds of trust to communicate messages and enact change. To date, there has been little consideration of the position and influence of newcomers to communities within this rationale. This paper explores this issue through two government-funded, community-led sustainability projects in rural Scotland. We observe that the majority of those most actively involved in these two projects had migrated to the communities and were considered 'incomers' by both themselves and other 'local' residents. Drawing these observations together with literature on rural migration and participation in community activity, we explore the potential implications for the outcomes of initiatives seeking to influence lifestyle change. We question whether projects that are established by, and primarily comprised of, individuals who are not necessarily considered 'locals' locally align with the rationale behind a 'community-led' approach.